A PAIRED STUDY: SABOURAUD'S MEDIA VERSUS DERMATOPHYTE TEST MEDIA - Haroon, Shahla; Tayyab, Mohammad; Gandapur, bdus Salam Khan (Journal of Ayub Medical College Abbottabad, 2000)
Background: Dermatophyte infection is very common, especially now a-days in immuno- suppressed host. As biochemical and serological system is not mature in isolation of fungi, we have to rely on microscopy and different media. In this study Dermatophyte Test Media (DTM) was compared with basic Sabouraud's media, to evaluate the claim that DTM can be used by untrained personal for dermatophyte identification. Methods: 110 cases were compared. Both medias were inoculated with specimens from same body site. Growth and color change were carefully noted. If growth was positive, a direct microscopy was done to identify the culture. Results: DTM was found slightly better in fungal isolations and in suppressing bacterial growth. It was found not to be as effective for easy identification as claimed by scientific workmen because false positive results are quite common and need experienced person for identification.